Impacts of turbine and plant upsizing on the levelized cost of energy for offshore wind. (15th September 2021) - Shields, Matt; Beiter, Philipp; Nunemaker, Jake; Cooperman, Aubryn; Duffy, Patrick
Abstract: Turbine and plant upsizing are major trends in offshore wind deployment, although the quantitative impact on project costs has not been well-characterized. The uncertain value of continued wind turbine and project growth limits the ability of the supply chain to prepare for future technology trends, leading to challenges in the realization of larger projects. This analysis explores the levelized cost of energy impacts of turbine ratings between 6 and 20 MW and plant capacities between 250 and 2, 500 MW for fixed-bottom offshore wind using techno-economic cost models for foundation, electrical, installation, and operation and maintenance costs, along with annual energy production. We consider a nominal set of technology assumptions for all scenarios to isolate economies of size and scale without additional benefits from decreasing turbine capital costs, quantity discounts for larger projects, or optimized technology solutions. These results indicate that using a 20-MW wind turbine in a 2, 500-MW power plant array can reduce the levelized cost of energy by over 23% relative to the global average turbine and plant size installed in 2019; primarily because of reductions in the balance-of-system and operation and maintenance costs. We also identify improved installation vessels, optimized export systems, and novel operation and maintenance strategies as additional cost reduction opportunities. These results suggest that upsizing represents a significant cost reduction opportunity for offshore wind energy and will continue to be a main factor in shaping the future of the sector. Highlights: The levelized cost of energy of offshore wind is impacted by turbine and plant size. Upsizing can reduce costs by over 23% relative to current technologies. Decreased balance-of-system and operational expenses drive these cost reductions. Technological innovations are required to enable or exceed these cost reductions.